2021
DOI: 10.1103/physrevmaterials.5.084410
|View full text |Cite
|
Sign up to set email alerts
|

Role of higher-order effects in spin-misalignment small-angle neutron scattering of high-pressure torsion nickel

Abstract: Magnetic-field-dependent unpolarized small-angle neutron scattering (SANS) experiments demonstrate that high-pressure torsion (HPT) straining induces spin misalignments in pure Ni, which persist in magnetic fields up to 4 T. The spin-misalignment scattering patterns are elongated perpendicular to the applied magnetic field due to an unusual predominant longitudinal sin 2 -type angular anisotropy. Such a contribution cannot be explained by the conventional second order (in spin misalignment amplitude) micromag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…The anisotropy value turns out to be rather large, K 0 ¼ 0 M 2 0 Q=2 ffi 2.6 Â 10 4 J m À3 (using M 0 = 482 kA m À1 ). It was silently absorbed into the S H ðqÞ and S M ðqÞ response functions in the work of Oba et al (2021) but can be revealed using the present more sophisticated theory; and it agrees very well with the value of 1.8 Â 10 4 J m À3 estimated by Bersweiler et al (2021) using a correlation-function analysis on the same specimen.…”
Section: High-pressure-torsion Nickelsupporting
confidence: 79%
See 3 more Smart Citations
“…The anisotropy value turns out to be rather large, K 0 ¼ 0 M 2 0 Q=2 ffi 2.6 Â 10 4 J m À3 (using M 0 = 482 kA m À1 ). It was silently absorbed into the S H ðqÞ and S M ðqÞ response functions in the work of Oba et al (2021) but can be revealed using the present more sophisticated theory; and it agrees very well with the value of 1.8 Â 10 4 J m À3 estimated by Bersweiler et al (2021) using a correlation-function analysis on the same specimen.…”
Section: High-pressure-torsion Nickelsupporting
confidence: 79%
“…Due to its inherent axial symmetry, high-pressure torsion (HPT) is another way to induce a uniaxial anisotropy in an originally isotropic sample. Oba et al (2021) report magnetic SANS cross section data (shown in Fig. 3) on an Ni sample subjected to such a treatment.…”
Section: High-pressure-torsion Nickelmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPT treatment of commercially pure nickel (99.6%) at liquid nitrogen temperature resulted in a nanostructure with an average grain size of 80 nm and a microhardness of up to 6200 MPa [ 30 ]. HPT strain was found to lead to spin misalignment in pure Ni by magnetic field-dependent unpolarized small-angle neutron scattering experiments and remains present in magnetic fields up to 4 T. The spin-misalignment scattering patterns are elongated perpendicular to the applied magnetic field due to the predominance of unusual longitudinal sin 2 θ-type angular anisotropy [ 31 ]. Different from Fe and Co, HPT has a more complicated effect on the magnetic properties of Ni.…”
Section: Application Of Hpt To Pure Magnetic Elementsmentioning
confidence: 99%